Design of a Taiji-like Dual-band Microstrip Patch Antenna Loaded with Bagua Parasitic Patch. (1st March 2023) - Wang, Shike; Xia, Dan; Lv, Lianrong; Qin, Juan; Wang, Meng; Chen, Mengdan; Wang, Biao; Li, Lei
Abstract: This study proposes a Taiji-shaped microstrip patch antenna without affecting its size and design complexity. The radiation patch adopts a Taiji-like shape design, and the traditional Chinese Bagua-shaped parasitic element is loaded on the periphery of the radiation patch on the surface of the dielectric substrate to optimize the impedance matching further and improve the gain. The software HFSS15.0 is used to simulate the antenna and compare the results. The results show that the antenna achieves dual-band characteristics at 2.45GHz and 5.04GHz, has an impedance bandwidth of 110MHz and 250MHz, and has a positive gain of 7.13dB. The proposed antenna is suitable for the field of wireless communication.